Correlation analysis of ground motion intensity measures for seismic damage assessment: insights from near and far field records - Sharma M.; Singh S.; Prasad P.; Anand V.; Islam N. (My University, 2025)
This study examines the relationship between various earthquake ground motion parameters, offering valuable insights into structural behaviour. The analysis utilizes the horizontal components of motion from 71 pairs of far-field and 98 pairs of near-field ground motion records sourced from the PEER NGA West-2 Database. Factors such as event magnitude, source-to-site distance, and geological conditions at recording sites are carefully taken into account. Seism Signal software is employed to determine the ground motion parameters. A particular focus is placed on investigating the correlation between different ground motion parameters, especially the ratio of peak ground acceleration (PGA) to peak ground velocity (PGV), which is a critical parameter for classifying ground motion suites in nonlinear time history analyses of structures. Using Pearson correlation, the study highlights that mean time exhibits the strongest correlation with the PGA/PGV ratio for far-source earthquakes. Additionally, it identifies a more pronounced correlation between the PGA/PGV ratio and specific ground motion parameters in near-source earthquakes compared to far-source events. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2025.